Reduced mental load in learning a motor visual task with virtual 3D method. (27th November 2017) - Dan, A.; Reiner, M.
Abstract: Distance learning is expanding rapidly, fueled by the novel technologies for shared recorded teaching sessions on the Web. Here, we ask whether 3D stereoscopic (3DS) virtual learning environment teaching sessions are more compelling than typical two‐dimensional (2D) video sessions and whether this type of teaching results in superior learning. The research goal was to compare learning in 2 virtual learning scenarios—on 2D displays and with an identical 3DS scenario. Participants watched a 2D or 3DS video of an instructor demonstrating a box origami paper‐folding task. We compared participants' folding test scores and self‐assessment questionnaires of the teaching scenarios and calculated their cognitive load index (CLI) based on electroencephalogram measurements during the observation periods. Results showed a highly significant difference between participants' folding test scores, CLI, and self‐assessment questionnaire results in 2D compared to 3DS sessions. Our findings indicate that employing stereoscopic 3D technology over 2D displays in the design of emerging virtual and augmented reality applications in distance learning has advantages. Lay Description: What is already known about this topic? Distance learning is expanding rapidly and recent innovations make stereoscopic three‐dimensional (3D) displays a new way to learn. Only a few studies have focused on an empirical test of the learning efficacy of 3D stereoscopic (3DS)‐virtual learning environments. Electroencephalogram measures of theta–alpha channels in frontal and parietal brain regions have been found to correlate with mental/cognitive load. What this paper adds? Cognitive load, based on electroencephalogram psychophysiological measures, is lower in a 3DS digital environment compared to a flat screen. Results showed a highly significant difference between participants' folding test scores, cognitive load index, and self‐assessment questionnaire results in two‐dimensional (2D) compared to 3D. 3DS virtual learning environment teaching sessions are more compelling than typical 2D video sessions and this type of teaching results in superior learning. Implications for practice and/or policy: Results show that learning is improved in the 3DS realistic human avatar compared to the 2D video. The relations between 2D and 3D displays in virtual reality and learning are potentially transferable to a series of principles for optimal practice in instructional design. Employing stereoscopic 3D technology over 2D displays in the design of emerging virtual and augmented reality applications in distance learning has advantages.